EFFECT OF MILLICHANNEL REACTOR MATERIAL ON BIODIESEL PRODUCTION FROM REFINED PALM OIL - WAN AB RASHID, WAN NORITA (2016)
In recent years, it is known that microchannel reactor has been studied for continuous synthesis of biodiesel. Although transesterification using micro size reactor gives high yield and conversion, microchannel reactor generally do not tolerate particulates well and often clogging. The clogging issue can be solved by using different size of tube which is larger than micro-size. At present, despite all the reported studies, there is currently no study which explore the performances of millisize reactor on the effects of reaction parameters. Therefore, the objectives of this study were to investigate the effects of reaction temperature, methanol to oil molar ratio, potassium hydroxide (KOH) concentration in methanol, and residence time on the oil conversion and fatty acid methyl ester (FAME) yield.